Rancang Bangun Pengenalan Modul Komunikasi dengan Konfigurasi Otomatis Berbasis UART - Mukmin Mukmin; Sabriansyah Rizqika Akbar; Dahnial Syauqy (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Wireless communication is a communication technology that uses electromagnetic waves to transmit signals with close distances and long distances. However, the use of wireless communication modules such as ESP8266 and NRF24l01 for wireless data transmission learning media for beginners who hadware use some microcontroller like Arduino constrained during initial configuration. From the problem it is necessary research about making wireless communication module that is Plug and Play (PnP) when connected with microcontroller like Arduino. In this research use 2 wirelesss communication module that is ESP8266 type E-01 and NRF24l01 and use serial communication (UART) to connect to microntroler like Arduino Uno. There is an ATmega 328P chip or ATtiny85 chip as an intermediary / serial communication control from ESP8266 or NRF24l01 to Arduino Uno acting as a core module. The design of communication module testing ESP8266 and NRF24l01 is done in 3 stages of introduction, selection, and transmission of PnP communication module data. In the introduction phase - the selection of communication module using Triple Handshaking process while in the data transmission phase for communication module ESP8266 using MQTT protocol and communication module NRF24101 using RF24 library to do data transmission. For the introduction phase module / handshaking 1 takes 1.5 while the module selection stage of handshaking 2 and 3 takes 0.2 seconds each time. The results of data transmission from 21 times the delivery of communication module is 100%. It is influenced by the delivery of data delivery delay, for ESP8266 given delay of at least 1.1 seconds while NRF24l01 given delay at least 1 second.